(3JfHjg GdeZJQjf aj GdbQf GdYGTQ Ydi eG NGdahG ajg Sdage GdWGgQs - (3GdnMnfaj GdnqTrYQGfj, CHh eMeO, YHO GdhqgGH Hf CMeO Hf Ydj, J(B973(3g`s
(3ChdgG (B:s
(3HYO GdHSedI jbhd eDdag YHO GdhgGHGdTYQGfj CMeO Gddg QH GdYGdejfhHYO agPG cJGH fajS LeYJ ajg fHPI UGdMI ef abg WQjb Cgd Gddg hSejJg JfHjg GdeZJQjfs
(3BNQgG (B:s
(3jG OGhhO ef YUGfj aj GdNdhGJ GWdYJ GdeNdhbjf Ydi eSGhF CYeGdg haVMJg hGONdJg GdfGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 180s
(3eYLe GdeDdajf(B: 2 / 339s
(3cTa GdXfhf(B: 1 / 488s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs